2012
DOI: 10.5130/ajceb.v12i2.2448
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the adoption of information technology in a construction business

Abstract: Construction firms are increasingly utilizing information technologies to better manage geographically dispersed projects. Often these technologies involve changes to existing working practices and processes and are viewed as disruptive by members of the organization. Understanding the factors that can influence individuals’ intention to utilize technology can assist managers to implement strategies to increase and improve the uptake of technologies and improve the innovation adoption process.  Using a case st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 41 publications
7
44
1
2
Order By: Relevance
“…Finally, management needs to support any technology adoption initiatives, for example encouraging employees to use the technology and demonstrating its benefits, similarly Gambatese & Hallowell (2011) and Sargent, Hyland, & Sawang (2012). The practical implications resulting from the resistance to change is that although it does not directly affect intention to adopt a new technology, it is a construct that definitely could prevent the general adoption of a technology.…”
Section: Managerial Implicationsmentioning
confidence: 98%
“…Finally, management needs to support any technology adoption initiatives, for example encouraging employees to use the technology and demonstrating its benefits, similarly Gambatese & Hallowell (2011) and Sargent, Hyland, & Sawang (2012). The practical implications resulting from the resistance to change is that although it does not directly affect intention to adopt a new technology, it is a construct that definitely could prevent the general adoption of a technology.…”
Section: Managerial Implicationsmentioning
confidence: 98%
“…Adapun menurut [20] ekspektasi-ekspektasi dan variabelvariabel yang dimaksudkan adalah variabel kinerja, variabel usaha, variabel sosial dan faktor fasilitas.…”
Section: Pendahuluanunclassified
“…Usman (2014) reviewed the key factors that affect the adoption of technology in the Nigerian construction firms and found that culture, policy, and cost are key to the adoption of technology. Sargent, Hyland, and Sawang (2012) investigated the factors influencing the adoption of information technology in the construction business and found that the intention of an individual to use information technology is influenced by top management support, internal facilitating conditions and effort expectancy. Also, the fear/ resistance to new ways (changes) influence the adoption of innovation.…”
Section: Introductionmentioning
confidence: 99%